Education trajectories: From early childhood to early adulthood in Peru - Cueto, S; Miranda, A; León, J; Vásquez, M (Young Lives, 2016)
Over the past few decades, every President in Peru has proclaimed education as a priority; yet, in spite of recent progress across several indicators, educational outcomes are still on average low, and gaps between students large and closely linked with their individual and family background. This paper looks at the education trajectories of children in different stages of life, using data from Young Lives, an international study that follows two groups of children: an Older Cohort (born in 1994) and a Younger Cohort (born in 2001). According to the Peruvian Constitution and General Education Law, education is considered a human right, and all students should have access to a quality service. However, results from our study and others suggest that while there have been important advances over the past two decades, there is still a long way to go for this to become a reality for everyone.